La última feria - Íscar, Ricardo; Paiva, Alê (Polar Star Films, 2015)
For all of us, life is a film with a predictable ending. With 7 billion future clients in mind, Spanish and Portuguese companies from the funeral sector meet every year in Ourense to show off their latest products and services. There are diamond-studded and mink-lined coffins, hardwood urns, Swarovski crosses as gifts and luxury cars for a high-class public. No, in death we are not all equal, although obviously it comes to the rich as it does the poor in the end. In The Final Fair, morbid fascination, dread and black humour are washed down with cava and Iberian ham.--